Sustainability Entrepreneurship Supply Chain in Family Business - Christina Nawangsari, Lenny; Hidayat Sutawijaya, Ahmad; Aima, Havidz Aima; Huiping, Huang (ExcelingTech, 2020)
A Family business is a company whose majority shareholder is a family, and the position of manager (management) is controlled by family members and it is expected that the family descendants will follow in their footsteps later as managers. In this context, the application of the concept of sustainable supply chain management in the operation strategy of small business seems to be an important function. This supply chain also covers all three aspects of sustainable development: business, environmental, and social. The purpose of this article is to present the current state of the research in sustainable development in relation to managing the supply chain of family business, as well as the empirical findings in this area. This research supposed to analysis of the comparison of Entrepreneurial supply chain and sustainability of family business in China and Indonesia. This research done with Quantitative Method using SEM / Generalized Structured Component Analysis (GeSCA) program by visiting and interviewing with Family business China and Indonesia. The population in this study was a sample of 100 people. The sampling technique is random sampling. This research proves: 1). Leadership, Culture and Innovation have a significant effect on the Entrepreneurial supply chain in Indonesia and China; 2). Leadership and Innovation have a significant effect in Family Business Sustainability. 3). The Entrepreneurial supply chain, Culture and Innovation have a significant effect on the Sustainability of the Family Business, whereas the Leadership is not significant on the Sustainability of the Family Business in China; 4). Entrepreneurial supply chain does not mediate the influence of Leadership, Culture and Innovation on the Sustainability of Family Businesses in Indonesia; but Entrepreneurial supply chain mediates the influence of Leadership, Culture and Innovation on the Sustainability of Family Businesses in China.